Social inequalities, debt, and health in the United States. (March 2021) - Batomen, Brice; Sweet, Elizabeth; Nandi, Arijit
Abstract: Background: Household financial debt has more than tripled since the 1980s in the United States. The experience of indebtedness is socially structured and there is mounting evidence that debt is linked to decrements in health. However, it is unclear whether debt contributes to social disparities in health. Objective: We examined whether household debt, measured by debt in excess of income and wealth, mediated education-based social inequalities in health, including cardiovascular risk factors (hypertension) and chronic conditions (diabetes, coronary heart disease, and psychiatric problems). Method: We used longitudinal data from a sample of over 10, 500 adults aged 18 years and older surveyed biennially between 1999 and 2015 as part of the Panel Study of Income Dynamics (PSID). We estimated the total effect of education on our health outcomes. To assess mediation by levels of household debt, we then estimated the controlled direct effect of education through pathways not mediated by levels of household debt, after accounting for lagged time-varying confounders and loss to follow-up using marginal structural models. Results: Compared to respondents with at least a high school education, respondents with less than a high school education reported higher household debts in excess of income and wealth; they also reported a higher incidence of hypertension [risk ratio (RR) = 1.25, 95%CI = 1.13, 1.39), coronary heart disease (RR = 1.42, 95%CI: 1.25, 1.62), diabetes (RR = 1.50, 95%CI: 1.34, 1.68), and psychiatric problems (RR = 1.39, 95%CI: 1.24, 1.56). Compared to the total effects, the controlled direct effects of education on health were attenuated, particularly for death or first onset of hypertension and coronary heart disease, after fixing levels of household debt-to-income and debt-to-wealth. Conclusion: Our results provide early evidence that household debt in excess of wealth partly mediates education-based inequalities in hypertension and coronary heart disease in the United States, with less consistent evidence for other chronic conditions. Highlights: Household debt has more than tripled since the 1980s in the United States. There is mounting evidence that debt is linked to decrements in health. We examined whether household debt mediated social inequalities in health. Household debt in excess of wealth partly mediates social inequalities in hypertension and coronary heart disease.